DESAIN MEDIA PEMBELAJARAN KEAMANAN DIGITAL UNTUK PELAKU UMKM DENGAN METODE USER CENTERED DESIGN (UCD) - Inayatul Ulya Ahyati; Rika Novyanti (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2023)
When entering the digital ecosystem, MSMEs become easy targets for cybercriminals. Therefore, apart from improving their security systems, MSME entrepreneurs must have digital safety competencies. Instructional media will make it easier for MSME entrepreneurs to learn digital safety independently. This research aims to create a digital safety instructional media prototype that suits MSME entrepreneurs’s need using the user-centered design (UCD) method. MSME entrepreneurs have various ages and abilities to use technology. It is hoped that by applying the UCD method, the resulting instructional media will be easy to use and meet user needs. UCD in this research consists of four activities, there are: identifying user needs, designing solutions, creating prototypes, and evaluation. The result of this research is an instructional media prototype that can display learning material, evaluate users understanding, and display evaluation results scores. This prototype was tested on participants using the single ease question (SEQ) metric. The average participant SEQ score was 5.9, which shows that the proposed instructional media design is easy to use. Most participants considered that the proposed design was attractive, provided easy access, and presented the material well.